IN VITRO PROPAGATION OF Renealmia alpinia (ROTTB), PLANT AGAINST SNAKEBITE. - ALARCÓN P., Juan C.; MARTÍNEZ R., Diego M.; QUINTANA C., Juan C.; JIMÉNEZ R., Silvia; DÍAZ C., Abel; JIMÉNEZ, Ivone (Vitae, 2009)
Renealmia alpinia (matandrea or achira de monte) it`s an important plant for their neutralizing ability of both effects oedema-forming, hemorrhagic and clotting of the venom of the snake Bothrops asper (mapaná equis). It is a potential alternative of primary attention in ofidic accidents, or like a source of molecules with pharmaceutical importance. Despite this, there is not previous studies on this specie guided to micropropagation, tissular dedifferentiation or in vitro metabolites production. In this work was evaluated some variables as the height, the number of shoots and roots in the propagation of R. alpinia under in vitro conditions, as well as the rate of speed multiplication and the induction of having undiferentiated tissue in foliar explants. Addition of 6-Bencylaminopurine (3 mg/L) promotes the propagation in vitro, with a rate of speed multiplication (TVM) of 1.39 shoots/week, while the induction of having undiferentiated tissue in foliar explants was favored by both 2,4-D (2 mg/L) and BA (1mg/L)in combination. Additionally, was detected in foliar tissues (of grown plants in vitro and in vitro) cumarins, its metabolites has been found in some plants with well-known antiofídic activity, this results open possibilities of studies in order to the production and in vitro activity evaluation of metabolites with potential antiofidic activity or pharmaceutical interest.